Citronellal reactions with ozone and OH radical: Rate constants and gas-phase products detected using PFBHA derivatization - Harrison, J.C.; Ham, J.E.; Wells, J.R. (Atmospheric environment (1994), 2007)
The bimolecular rate constants, k OH+citronellal, (150±40)×10 −12 cm 3 molecule −1 s −1 and, k O 3 + citronellal , (3.5±1.2)×10 −16 cm 3 molecule −1 s −1, were measured using the relative rate technique for the reactions of the hydroxyl radical (OH) and ozone (O 3) with 3,7-dimethyl-6-octen-1-al ((R)-(+)-citronellal) at (297±3) K and 1 atm total pressure. To more clearly define part of citronellal's indoor environment degradation mechanism, the products of the citronellal+OH and citronellal+O 3 reactions were also investigated. The positively identified citronellal/OH and citronellal/O 3 reaction products were: 3-methylhexanedial HC( O)CH 2CH 2CH(CH 3)CH 2C( O)H and 2-oxopropanal (methylglyoxal, CH 3C( O)C( O)H). The use of derivatizing agent O-(2,3,4,5,6-pentafluorobenzyl)hydroxylamine (PFBHA) was used to propose 3-methylhexanedial as a major citronellal/OH and citronellal/O 3 reaction product. The elucidation of this reaction product was facilitated by mass spectrometry of the derivatized reaction products coupled with plausible citronellal/OH and citronellal/O 3 reaction mechanisms based on previously published volatile organic compound/OH and volatile organic compound/O 3 gas-phase reaction mechanisms.